HUBUNGAN DUKUNGAN SOSIAL DAN INTERAKSI IBU-ANAK DALAM MENINGKATKAN KESEJAHTERAAN SUBJEKTIF REMAJA PADA KELUARGA ORANG TUA BEKERJA DI DESA GELAM KUTAJAYA - Yuspita, Sri; Kamil, Ikhsan; Ratnasari, Febi (Nusantara Hasana Berdikari, 2021)
The level of subjective well-being of adolescents can be used to identify problems that occur in adolescents from an early age and make preventive actions so that quality adolescents are formed. Social support and mother-child interaction are also very important in identifying problems that occur in children, but with adolescents who have intact parents and both work very little time to interact with children. The less interaction with children and less good, the lower subjective well-being, but if the interaction between children is good it can increase subjective well-being higher. The purpose of this study was to determine the relationship between social support and mother-child interaction in improving the subjective well-being of adolescents in working parents' families. The results of the research data analysis used were univariate and bivariate analysis using the chi square test and the correlational rank spearmanas evidenced by the statistical test results that there was a relationship between social support and subjective well-being, p value 0.000 with r 0.284 means that there is a low close relationship. Then there is a relationship between mother-child interaction with subjective well being, p value 0.000 with r 0.324 means that there is a low close relationship.